MERCURY SPECIATION IN SOILS OF THE INDUSTRIALISED THUR RIVER CATCHMENT (ALSACE, FRANCE) - Remy S.; Prudent P.; Probst J.-L. (My University, 2006)
Methylmercury (MeHg) and total Hg (THg) concentrations in soil profiles were monitored in the Thur River basin (Alsace, France), where a chlor-alkali plant has been located in the city of Vieux-Thann since the 1930s. Three soil types were studied according to their characteristics and location in the catchment: industrial soil, grassland soil and alluvial soil. Contamination of MeHg and THg in soil was important in the vicinity of the plant, especially in industrial and alluvial soil. Concentrations of MeHg reached 27 ng g-1 and 29,000 ng g-1 for THg, exceeding the predictable no effect concentration. Significant ecotoxicological risk exists in this area and remedial actions on several soil types are suggested. In each type of soil, MeHg concentrations were highest in topsoil, which decreased with depth. Concentrations of MeHg were negatively correlated with soil organic matter and total S, particularly when MeHg concentrations exceeded 8 ng g-1. Under these conditions, MeHg concentrations in soil seemed to be influenced by THg, soil organic matter and total S concentrations. It was found that high MeHg/THg ratios (near 2%) in soil were mainly related to the combined soil environmental conditions such as low THg concentrations, low organic C/N ratios (<11) and relatively low pH (5-5.5). Nevertheless, even when the MeHg/THg ratio was low (~0.04%), MeHg and THg concentrations were elevated, up to 13 ng g-1 and to 29,000 ng g-1, respectively. Thus, both THg and MeHg concentrations should be taken into account to assess potential environmental risks of Hg. © 2006 Elsevier Ltd. All rights reserved.